To establish if after-sales support is a determining factor in the purchase of fitness equipment, and examine, review, and provide recommendations on how Cybex Inc.ÃÂÃÂ¢ÃÂÃÂÃÂÃÂs approach to worldwide after-sales should be re-engineered to meet the ever increasing expectations of new and existing customers. - Withey, Simon (2006)
Cybex Inc. is a worldwide supplier of commercial fitness equipment, operating in a highly competitive market, where the products supplied by the 5 main producers worldwide (including Cybex Inc.) are homogenous offering limited points of differentiation to the end consumer.